Traumatic ulcer distribution of patiens with removable orthodontic appliance in Orthodontics Clinics of Dental Specialist Program - Akbari, Gusti; Dewi, Tenny Setiani; Malik, Isnaniah (Padjadjaran Journal of Dentistry, 2014)
Introduction: Treatment with fixed orthodontic appliance sometimes cause the oral mucosa lesion, known as a traumatic ulcer. The purpose of this research is to see the distribution of traumatic ulcer on the patient with a fixed orthodontic appliance in PPDGS Orthodontic RSGM FKG Unpad Clinic. Methods: This research used a descriptive observational method. The sample of this research consisted of 39 people who participate in the interview and willing to be examined the condition of their oral mucosa during the study. Results: Twenty three samples or about 59% from all the sample have a traumatic ulcer on the oral mucosa. Conclusion: Most of the patient with a fixed orthodontic appliance has a traumatic ulcer, which mostly located on the buccal mucosa, followed by labial mucosa, and gingiva.